Long-Term Functional and Anatomical Outcome of Radial Optic Neurotomy for Central Retinal Vein Occlusion - Konstantinidis, L.; Bissig, A.; Pournaras, J.-A.; Wolfensberger, T. J. (Klinische Monatsblätter für Augenheilkunde, 2016)
Background: Without treatment, the natural history of central retinal vein occlusion (CRVO) can result in severe loss of vision. Material and Methods: This was a retrospective study of 10 eyes with CRVO treated with pars plana vitrectomy (PPV), combined with radial optic neurotomy. The patients completed a minimum of 5 years follow-up. Results: Median age at the time of surgery was 67 ± 14 years. Median follow-up was 79 ± 9 months. Ischaemic changes were present in 4 patients pre-operatively. Baseline median logMAR BCVA was 2.00 ± 0.76 and improved significantly to a median of 0.35 ± 0.54 (p < 0.0001, two tailed t test) at 5 years follow-up. The baseline median central macular thickness (CMT) was 645 ± 108 µm and improved significantly, to a median of 203 ± 72 µm (p < 0.0001, two tailed t test). One of the patients developed neovascular complications during the follow-up period. Conclusions: Our results compare very favorably with the natural history of CRVO. All patients demonstrated a trend to improved visual acuity, while only one of the patients developed neovascular complications. These results provide information on the potential long-term effect of PPV in patients with CRVO and may help to reassess the place of the surgical management of CRVO in patients who do not respond to medical treatment.
Keywords: central retinal vein occlusion; pars plana vitrectomy; radial optic neurotomy